Housing conditions and broiler and broiler breeder welfare : the effect of litter condition on contact dermatitis in broilers and broiler breeders, and the effect of elevated structures on broiler leg health - Kaukonen, Eija; Helsingin yliopisto. Eläinlääketieteellinen tiedekunta (University of Helsinki, 2017)
English abstract.
Keywords: Broilers (Chickens); Poultry : Housing; Chicken industry; broilerit; siipikarja; emot; jalat; ihotaudit; ihottumat; kanalat; kuivikkeet; broilrar; fjäderfä; djurmödrar; ben (extremiteter); hudsjukdomar; hudutslag; hönshus; torrströ